A Study on Accessibility of Disabled People: Case for Kızılay Shopping Center, Ankara - Hayri Ulvi (Iconarp International Journal of Architecture and Planning, 2019)
Although legal arrangements have been made about accessibility in Turkey, their reflection the urban spaces have been inadequate. Accessibility is an issue that needs to handle at different scales to improve the quality of life of every individual disabled or not. Analyzing many studies, it is observed that the disabled people in the society have difficulty in either inside of place or outside of place accessibility. It is among the most important accessibility problems that the design of the place with standard measures that will increase the accessibility of individuals is ignored. In order to draw attention to the planning and design criteria on the accessibility of place, it is aimed to determine the accessibility of the space by analyzing compliance with standards in Ankara Kızılay shopping center case area. Within the scope of the study, accessibility criteria in the study area are evaluated by using an accessibility monitoring and inspection form for buildings prepared by the Ministry of Family and Social Policies General Directorate of Disabled and Elderly Services. As a result of the evaluation, it is revealed how accessible the components that affect the availability of Kızılay AVM. According to this study, there is no usage area with very poor accessibility level. Parking has poor accessibility level. The use of emergency and building installation elements is at the medium level of accessibility. Perceptible walking surface signs and building entrances have good accessibility levels. The other usage areas of the shopping center are horizontal and vertical circulation in the building, toilets and orientation and markings are very well accessible. The importance of this study is the answer to the question how accessible the social activity area for all in Kızılay, which is developed as the central business area of Ankara over the accessibility criteria according to legislation.